Energy-absorption characteristics of a circumferentially corrugated square tube with a cosine profile. (February 2019) - Li, Zhixiang; Yao, Shuguang; Ma, Wen; Xu, Ping; Che, Quanwei
Abstract: This paper proposes a new circumferentially corrugated square tube (CCST) with a cosine profile. The cross section of the CCST is controlled by a cosine expression with parameters that include the number ( N ) of cosine wave crests, the amplitude ( A ) and the nominal side length (2 L 0 ). Finite element (FE) models validated by experimental results were constructed in Ls_dyna to analyse the crashworthiness performance of the CCSTs. The numerical results show that the collapse modes of CCSTs are classified into five types, i.e., non-ordered progressive mode (NPM), ordered progressive mode (OPM), inversion mode (IM), global buckling mode (GBM) and extensional mode (EM). After analysing the collapse characteristics, force-displacement characteristics and crashworthiness indexes, we found that the OPM has better crashworthiness performance than the other modes. Moreover, a more comprehensive parametric study was conducted to understand the effects of the geometric parameters N, A and wall thickness ( t ) on the crashworthiness performance of CCSTs. The results show that the collapse modes of CCSTs are fairly sensitive to the cross-sectional configuration and wall thickness. Increases in N, A and t all cause increases in the initial peak crushing force ( IPCF ), and the wall thickness t has the most significant effect on IPCF . However, the effects of the three geometric parameters on specific energy absorption ( SEA ) are much more complicated and are largely dependent on whether the collapse modes change or not with increases in the three parameters. The numerical results also show that the SEA of CCSTs is improved by 51.62% compared with that of a square tube (ST) when they have the same mass (55.3 g) and by 69.24% when they have the same wall thickness ( t = 1.25 mm). These results reveal that CCSTs with OPM have good energy absorption ability. Highlights: A corrugated square tube (CCST) with a cosine profile is designed. The collapse modes of CCSTs are classified with numerical method. The effects of geometry parameters of CCST on crashworthiness performance are discussed.